Letter from Carl D. Duncan to Patricia Whiting, November 10, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan expresses his opinions on the Vietnam War, taking a moderate anti-war position. The typed portion of the letter is a separate letter to the local draft board expressing his opposition to the draft of young men while still attending college.